Analisis Hukum Persaingan Usaha Di Pasar Tradisional Tanah Abang Dengan Pasar Digital Platform Tiktokshop - Hilma Harmen; Dina Aulia; Marsela Natalie Hutape; Nadya Viska Harahap; Najwa Aulia Putri Hasibuan; Zsevta Samuel (CV. ULIL ALBAB CORP, 2024)
This study aims to understand the dynamics of competition between the traditional Tanah Abang market and the digital platform TikTok Shop in the context of competition law in Indonesia. The competition between Tanah Abang’s traditional market and digital platforms such as TikTok Shop shows significant dynamics due to changing consumer preferences, which are increasingly shifting toward online shopping. Although both are governed by the same laws concerning the prohibition of monopolistic practices and unfair competition, there are fundamental differences in the forms of competition and the application of sanctions. The traditional market relies on direct interaction and personal relationships between traders and buyers, while TikTok Shop utilizes technology and algorithms to enhance market reach and product promotion. Violations of competition in the traditional market often occur in the form of price manipulation and cartels, while in TikTok Shop, violations are related to the misuse of algorithms and unfair paid advertising. Strict law enforcement and stronger supervision are required to maintain healthy competition in both markets, protect consumers, and support small and medium enterprises to compete fairly in an increasingly digitalized era.